A cardiopulmonary bypass strategy to support a patient with vein of Galen malformation. (July 2022) - Robertson, Alex; Muthialu, Nagarajan; Broadhead, Mike
We present a dissection of the patent ductus arteriosus and pulmonary artery for surgical repair utilising cardiopulmonary bypass in the setting of vein of Galen malformation. Several strategies were employed to attenuate the cerebral shunt including pH-stat, high cardiac index, restrictive venous drainage, continuous ventilation and deep hypothermic circulatory arrest. The patient recovered from surgery with no apparent neurological sequelae.